Appraising Kinetic Approach to Counter-Terrorism in the Post-Cold War Era - Sekibo, George Thompson; Ojo, Olusola Matthew; Weinoh, Oboromeni; Madu, Mavis B. (NIU Journal of Social Sciences, 2024)
This paper examines the kinetic approach to counter-terrorism, which emphasises military force and direct action in the post-Cold War era. It assesses the effectiveness, challenges, and ethical considerations of this strategy, using case studies such as Operation Neptune Spear and drone strikes in Pakistan and Yemen. The study highlights the need for integrating kinetic methods with non-kinetic strategies to effectively combat the complexities of the modern while also addressing the adverse consequences, such as collateral damage and civilian casualties, which can lead to increased radicalisation and anti-American sentiment. The methodology adopted for this research is a qualitative method, where scholarly literature comprehensively assesses the kinetic approach, emphasising the need for integrating non-kinetic methods like intelligence gathering, counter-radicalisation programs, and socio-economic development to tackle the root causes of terrorism. Five theories, including Clausewitz’s Theory on War, Deterrence Theory, International Relations Theories on Realism and Liberalism, and ethical philosophy Theory on Just War, were used to analyse the effectiveness or otherwise of the approach. Findings revealed that while kinetic counter-terrorism operations, including military interventions and drone strikes, are effective in achieving immediate tactical goals by eliminating high-value targets and disrupting terrorist networks, their long-term strategic effectiveness is limited. This integrated strategy is crucial for achieving sustainable security and long-term stability. The study put forward valuable recommendations for Practice or Policy and suggestions for future research. Keywords: Counter-terrorism, Kinetic approach, Post-Cold War, Military force, Terrorism, Non-kinetic strategies